Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Steinmann, Paul; Striewe, Marius; Meschut, Gerson (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik, 2022)

Testing, modelling, and parameter identification for adhesively bonded joints under the influence of temperature - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik; Hein, David; Steinmann, Paul (Journal of Adhesion Science and Technology, 2022)
Epoxy resin adhesives are widely used in lightweight and structural applications and their mechanical properties are strongly temperature-dependent. In this study, shear and butt joint specimens are tested under quasi-static loading within a temperature interval from −40 to 80 °C to determine the influence of temperature on the mechanical properties of adhesively bonded joints. In addition to the experimental studies, the highly nonlinear inelastic Toughened Adhesive Polymer (TAPO) material model is extended by defining the model parameters as functions of temperature. The experimental results are then used to parameterize the extended model such that it can be used in Finite Element simulations. The main results are: For both load cases the yield stresses as well as the maximum stresses reach their maxima at the lowest temperature and decrease continuously with increasing temperature. The critical strain at maximum stress and also the failure strain increase with rising temperature. The energy absorption is generally higher under shear load than under tensile load. Due to interactions between parameters of the TAPO model which can lead to ambiguous solutions, the identification of temperature functions for the parameters is a challenge. The isolation of interacting parameters as well as the introduction of dependencies are used to effectively limit such interactions. The measures taken lead to a multistep procedure of alternating parameter identification and fitting of temperature functions. Simulations with the calibrated extended TAPO model show very good agreement with the experimental data for all temperatures.<br